Poltergeist II and III : double feature [videorecording (DVD)]. - Sherman, Gary A., 1945-; Williams, JoBeth; Nelson, Craig T.; O'Rourke, Heather, 1975-1988; Skerritt, Tom; Allen, Nancy, 1950 June 24- (Metro-Goldwyn-Mayer, 2015)
Poltergeist II: After moving to a new house, the Freelings discover that evil spirits are still trying to get to their young daughter.